(untitled) (Bangladesh Journal of Dental Research & Education, 2014)
Since the development of the ruby laser by Maiman in 1960, many lasers are available today for clinical application in dentistry, based on minimally invasive (Ml) dental treatment in routine clinical procedures including dental cavity preparation, removal of dental calculus, caries prevention, and treatment of dentin hypersensitivity, anti-iriflammation for soft tissues, pain relief, surgical operations, and hemostasis. Dental treatment using a laser is a minimally invasive, painless treatment with a low burden on the patient, and may therefore be seen as a treatment that complies with the Ml concept. However, safe use of lasers must be the underlying goal of proposed or future laser therapy. To ensure that safe, effective Ml treatment is practiced when using lasers, it is essential to have a full understanding of their advantages and disadvantages before using them. DOI: http://dx.doi.org/10.3329/bjdre.v4i2.20257 Bangladesh Journal of Dental Research and Education Vol.4(2) 2014: 91-93